Storytelling: The effects of corporate stories on the appreciation of organizations - Scheerder, Anique; Karreman, Joyce; de Jong, Menno (IPCC proceedings (Print), 2017)
Organizations increasingly resort to corporate stories in order to positively influence their stakeholders' perceptions. However, no substantive results are available that prove the effects of corporate stories. Apart from that, recommendations on which content elements should be included in corporate stories, nearly all rely on conceptual theories and not on empirical studies. The first goal of this study is to test whether corporate stories have more positive effects on the appreciation of organizations than a plain, factual summary of corporate information. The second goal is to take the first steps towards composing guidelines on what comprises a good story. Based on an online experiment among 201 participants, the effects of corporate stories as compared to corporate information on the appreciation of organizations were measured, in the context of a for-profit and a not-for-profit organization. Subsequently, the effects of including the elements `conflict' and `character' were examined. The results indicated that the effects of a story were less beneficial than expected. Statistical tests showed only a few differences between participants who read corporate information and those who read a story. In addition to that, no effects were found for the presence of a conflict and a character in a corporate story.